Not cat-scratch disease: Bartonella henselae neuroretinitis associated with non-feline pet mammals. (2020) - Orellana-Rios, Jorge; Verdaguer-Diaz, Juan I.; Opazo, Gabriela; Leong, Belinda C.S.; Zett, Claudio; Smith, R. Theodore; Freund, K. Bailey
Highlights: Bartonella henselae -associated neuroretinitis is an ocular complication of cat-scratch disease. The cat flea is the main vector to transmit Bartonella henselae although it is also found on other animals. As cat fleas may reside on non-feline hosts, pet mammals may act as carriers of Bartonella henselae. Neuroretinitis may result from contact with infected fleas on family pets. Abstract: To describe the ocurrence of Bartonella -associated neuroretinitis secondary to non-feline pet exposure, we retrospectively reviewed medical records and imaging from patients with a clinical and serologic diagnosis of Bartonella henselae (BH). Retinal imaging included color fundus photography, optical coherence tomography (OCT) and fluorescein angiography (FA). Four eyes of two patients with cat-scratch disease were included in this study, with a mean age of 35 years. The mean follow-up was 13 months, after presentation of infectious neuroretinitis. Both patients suffered from bilateral neuroretinitis after direct contact with family pets (ferret and guinea pig). All patients were treated with a long-term systemic antimicrobial therapy. Visual acuity in all improved to 20/30 or better at six months. In conclusion, humans may develop cat-scratch disease when they are exposed to Bartonella henselae (BH) in the saliva of infected cats or BH-containing flea feces reaching the systemic circulation through scratches or mucous membranes. As the cat flea ( Ctenocephalides felis ) may reside on non-feline mammals, Bartonella -associated neuroretinitis may result from contact with other furred family pets.